The history of America told by its men. The configuration of the Latin American native from the Martian perspective in various texts of La Edad de Oro (Islas, 2021)
Martí’s literature for children has been studied over the years by critics from Cuba, Latin America and many overseas regions. This type of literature cultivated by the Apostle offers dissimilar edges to be fully studied, especially from a perspective of reinvindication for the child subject. One of the most interesting and yet less studied points, in all its dimensions, is the presentation of the native in Martí's literary work dedicated to children. For such reason this article is presented. In order to conduct the research successfully, our fundamental objective is to carry out an analysis of the literary and philosophical mechanisms that José Martí used to present the Latin America native as a cultural subject. To fulfill the aforementioned objective, the studies conducted mainly by the Centro de Estudios Martianos have been taken into account due to their updating and relevance, as well as published articles related to the subject in question and its representation in Latin American literature and culture. Moreover, the stories from La Edad de Oro in which the native, and their traditions and cultural manifestations are best portrayed- have been selected. The aim of this study is to locate and culturally characterize the Latin American native within the work of Martí.
Keywords: indigenous subject